Extreme Volatility and Market Testing of Efficiency on Small Cap Indices - L. S., Sridhar; M., Sumathy (Journal of Commerce and Trade, 2016)
We examined the volatility and market efficiency countries small cap indices and also tested the relationship exists between emerging and developed countries small cap indices. The data consisted of daily series of International market Small-Cap indices which are from MSCI (Morgan Stanley Capital International) are used for analysis. The market index series were measured in dollar currency terms and no major discrepancies were found in the data. The study period is from 2009 to 2015 and the historical data used leading emerging countries such as Brazil, China, India, Indonesia, Korea, Malaysia, Philippines, Russia, South Africa and Taiwan and leading industrialized countries such as Australia, Belgium, Finland, France, Germany, Italy, Netherland, Norway, Switzerland and United Kingdom. We found that the industrialized countries have the market efficiency, it means the present price does not influence by the past price, whereas the emerging countries does not have the same. The volatility most of the countries have the reasonably long persistence of volatility.